Application of secondary steel slag in subgrade: Performance evaluation and enhancement. (20th April 2018) - Gu, Xingyu; Yu, Bin; Dong, Qiao; Deng, Yongfeng
Abstract: Steel slag accumulates heavily in China and has caused significant environmental burdens. In this study, secondary steel slag (SSS) was used a potential material in subgrade treatment. This study first blended SSS of different contents with lime soil and inspected the performances of the mixes in terms of compactability, strength and expansion ratio. The optimum treatment effect was obtained at a proportion of 50% SSS, 45% soil and 5% lime. Scanning electron microscopy test was conducted to reveal the strength development of SSS lime soil. The components of SSS were then supplemented by lime and metakaolin referring to the oxide compositions and proportions of the Portland cement. The unconfined compressive strength (UCS) of the reconstituted SSS increased from 0.73 MPa (plain SSS) to 4.09 MPa at 28d. Three agents, NaOH, NaCl and Na2 SO4, were selected to further improve the activity of the reconstituted SSS. At the content of 5%, the UCSs of the specimens activated by NaCl and Na2 SO4 increased to 8.02 MPa and 10.88 MPa at 28d, respectively. The reconstitution and activation of SSS is an effective way to improve the performance in subgrade treatment.